INCLUSION OF BOYS AND GIRLS WITH ASD AT THE LEVELS OF THE SECOND CURRICULAR SECTION OF PARVULAR EDUCATION: CASE STUDY OF AN EDUCATIONAL CENTER IN CHILE - Gárate Vergara, Francisco; Alejandra Jara Escobar, Constanza; Belén Maldonado Roblero, Tiare; Denisse Salazar Vásquez, Karin; Andrea Saldias Baeza, Carolina (Revista Gênero e Interdisciplinaridade, 2024)
This research is focused on the inclusion of children diagnosed with autistic spectrum disorder in early childhood education, which seeks to generate the equity of opportunities for everyone from the inclusive approach, adapting learning strategies to deliver quality learning and integral. This research is mixed approach and will answer the research question: how do the strategies use the nursery educators to work the inclusion with children diagnosed with ASD, in the 2nd curricular section of Pluvular Education? The teacher training that also possess the presumed to are appropriate to the needs of each child. We can indicate that despite all the advances, there are no necessary resources to include each child diagnosed with ASD. All these points mentioned above seek to respond to the barriers to the learning and participation existing within the 2nd Curriculum section of Plvular Education in Chile.